Wheat lines, suffering structural rearrangements between wheat-1BS and rye-1RS chromosomes, display differential patterns of magnesium accumulation - Gualano, Leonardo D.; Moriconi, Jorge I.; Tranquilli, Gabriela; Santa-Maria, Guillermo E. (Sociedad Argentina de Fisiología Vegetal, 2023)
Poster no. 238